Liquid crystal emulsion micro-droplet WGM resonators - Ježek, Jan; Pilát, Zdeněk; Brzobohatý, Oto; Jonáš, Alexandr; Aas, Mehdi; Kiraz, Alper; Zemánek, Pavel (SPIE, 2014)
We introduce tunable optofluidic microlasers based on optically stretched or thermally modified, dye-doped emulsion droplets of liquid crystals (LC) confined in a dual-beam optical trap. Droplets were created in microfluidic chips or by shaking. Optically trapped microdroplets emulsified in water and stained with fluorescent dye act as an active ultrahigh-Q optical resonant cavity hosting whispering gallery modes (WGMs). Tuning of the laser emission wavelength was achieved by a controlled deformation of the droplet shape using light-induced forces generated by dual-beam optical trap and by thermal changing of the order in the LC.
Keywords: Physics; Droplets; Liquid crystals; Microfluidic chips; Optical trapping; Whispering gallery modes